ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN GENERASI Z UNTUK MENGGUNAKAN JASA BANK SYARIAH (STUDI KASUS DI KELURAHAN BULURAN KENALI KECAMATAN TELANAI PURA KOTA JAMBI) - Dia Sartika; Addiarrahman; Sri Rahma (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2023)
Islamic banking is the most developed Islamic financial industry in Indonesia compared to the Islamic capital market industry and the Islamic non-bank financial industry. One of the potential market segments is the Generation Z community segmentation because it is a generation that is at a productive age. This study aims to determine the influence of product, promotion, and location, partially and simultaneously on the decision to use Islamic bank services in Buluran Kenali Village, Jambi City. This research approach uses a quantitative descriptive approach. Data were collected using questionnaires and field observations. The results showed that partial product, promotion, and location influenced the decision to use Islamic bank services in Buluran Kenali Village, Telanai Pura District, Jambi City. Simultaneously, product, promotion, and location variables influence the decision to use Islamic banking services in Buluran Kenali Village, Telanai Pura District, Jambi City with a percentage of 82.5%.